2020
DOI: 10.1038/s41431-020-0640-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life drives patients’ preferences for secondary findings from genomic sequencing

Abstract: There is growing impetus to include measures of personal utility, the nonmedical value of information, in addition to clinical utility in health technology assessment (HTA) of genomic tests such as genomic sequencing (GS). However, personal utility and clinical utility are challenging to define and measure. This study aimed to explore what drives patients’ preferences for hypothetically learning medically actionable and non-medically actionable secondary findings (SF), capturing clinical and personal utility; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Parents also described feelings of responsibility toward their children and desires for control associated with receiving the results [ 11 ]. In contrast, adult participants want SSR in order to have greater certainty about personal risk [ 8 , 30 ], to determine whether they required screening [ 8 ], because it was recommended by their healthcare professional or desired by a relative [ 8 ], or for insurance or planning purposes [ 8 , 30 , 88 ]. Participants also listed a desire to know health information [ 5 , 12 , 81 ], provide diagnostic certainty [ 82 ], prevent disease/improve health [ 5 , 12 , 81 , 86 , 88 ], adopt better health habits [ 88 ] and alter medical management as reasons for wanting their results [ 5 , 82 ].…”
Section: Views On Return Of Study-specific Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents also described feelings of responsibility toward their children and desires for control associated with receiving the results [ 11 ]. In contrast, adult participants want SSR in order to have greater certainty about personal risk [ 8 , 30 ], to determine whether they required screening [ 8 ], because it was recommended by their healthcare professional or desired by a relative [ 8 ], or for insurance or planning purposes [ 8 , 30 , 88 ]. Participants also listed a desire to know health information [ 5 , 12 , 81 ], provide diagnostic certainty [ 82 ], prevent disease/improve health [ 5 , 12 , 81 , 86 , 88 ], adopt better health habits [ 88 ] and alter medical management as reasons for wanting their results [ 5 , 82 ].…”
Section: Views On Return Of Study-specific Resultsmentioning
confidence: 99%
“…May become overly vigilant/lead to unnecessary appointments [88] Inability to make health changes [85] Concerns about availability of health or life insurance [ Do not consider themselves to be at risk [97] Lack of resources and clinical expertise [94] https://doi.org/10.1371/journal.pone.0258646.t005…”
Section: Potentialmentioning
confidence: 99%
“…As a hypothesis, this remark may be justified by symptomatic echoing and experienced confrontations with the limits of coping strategies for IRD. www.nature.com/scientificreports/ Concerning the psychological consequences of UFs, the possibility of distress has been identified as an important motive against disclosure in this and other studies 13,16,33 . People may not want to receive too many UFs and, instead, prefer a partly open future 30,34 .…”
Section: Discussionmentioning
confidence: 66%
“…28 Previous research has found that participants value learning a broad range of genomic results, beyond results that are clinically actionable. [29][30][31][32] It is unknown how returning this information to patients with COVID-19 will impact patients' well-being and behaviour, and ultimately how these factors may impact the healthcare system (eg, health service utilisation). While previous studies have assessed return of results among patient populations affected by hereditary conditions, 33 34 less work has addressed return of results in the general population.…”
Section: Open Accessmentioning
confidence: 99%